2018
DOI: 10.1515/cogsem-2018-2002
|View full text |Cite
|
Sign up to set email alerts
|

Holistic spatial semantics and post-Talmian motion event typology: A case study of Thai and Telugu

Abstract: Leonard Talmy’s influential binary motion event typology has encountered four main challenges: (a) additional language types; (b) extensive “type-internal” variation; (c) the role of other relevant form classes than verbs and “satellites;” and (d) alternative definitions of key semantic concepts like Motion, Path and Manner. After reviewing these issues, we show that the theory ofHolistic Spatial Semanticsprovides analytical tools for their resolution. In support, we present an analysis of motion event descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…Aiming to contribute to this quest, the authors used a particular theoretical model, Holistic Spatial Semantics (HSS), aiming to show that it is capable of addressing challenges such as those stated in the previous paragraphs. In support of this claim, Naidu et al (2018) showed that Thai and Telugu speakers used significantly different patterns in the expression of self-motion events, and thus that the two languages cannot coalesce into a third "equipollent type". At the same time, both languages differ substantially from the two original Talmian types, exemplified by languages like Swedish and French, respectively.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Aiming to contribute to this quest, the authors used a particular theoretical model, Holistic Spatial Semantics (HSS), aiming to show that it is capable of addressing challenges such as those stated in the previous paragraphs. In support of this claim, Naidu et al (2018) showed that Thai and Telugu speakers used significantly different patterns in the expression of self-motion events, and thus that the two languages cannot coalesce into a third "equipollent type". At the same time, both languages differ substantially from the two original Talmian types, exemplified by languages like Swedish and French, respectively.…”
Section: Introductionmentioning
confidence: 90%
“…Hence, in the last decade or so the field can be said to have moved into a "post-Talmian" terrain of motion typology research (Naidu et al 2018), with various proposals on how to develop a better model. Least radical are those, such as that of Slobin (2004), to extend the typology with a third, "equipollently-framed" type, where Path and Manner of motion are expressed in structurally similar ways, as by different verbs in serial-verb constructions in Thai.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations